Drivers of plant richness patterns of Mediterranean riparian forests at local and regional scales have bottom‐up and top‐down effects. (2nd May 2019) - Leo, María; Calleja, Juan A.; Lara, Francisco; Garilleti, Ricardo; Medina, Nagore G.
Abstract: Questions: It has been long recognized that community species richness depends on factors operating at different spatial scales. Most frequently, across‐scale studies have focused on the impact of regional factors on local richness (top‐down effects) while few have analyzed the importance of local factors on regional richness (bottom‐up) and even fewer have tried to integrate effects on both directions. Our objectives were to reveal the key factors shaping plant species richness of Mediterranean riparian forests and to test whether empirical models based on top‐down or bottom‐up relationships are able to explain the spatial scaling of richness. Location: Southern half of Spain, SW Europe. Methods: We designed two structural equation models integrating relationships between biotic and abiotic variables at two spatial scales, local and regional. Our models incorporated observed richness of 689 riparian woody communities. Results: Local‐scale richness depended mostly on local climate, lithology and sediment textures. Regional species richness was driven by climate, lithology and water regime. In the top‐down model, regional to local effects were driven mostly by the influence of regional richness on local richness. However, we also detected several bottom‐up effects linking local climate, abiotic habitat and vegetation structure with the regional richness. In the bottom‐up model, results were very similar, adding an effect of regional climate on local richness. Conclusions: Local, regional and across‐scales factors are crucial for understanding species richness of Mediterranean riparian forests. Some factors are inherent to riparian habitats whereas others are already known as relevant for upland habitats. We provide support for the top‐down models relying on the concepts of species pool and environmental filtering. However, we also stress that local‐scale processes influence regional species richness. Bottom‐up effects should not be underestimated when studying the spatial scaling of biodiversity. Abstract : Community species richness depends on factors operating at different spatial scales. We attempted to seek the key factors shaping plant species richness of Mediterranean riparian forests and also the framework they are operating within to explain the spatial scaling of richness. Our findings suggest that local, regional and across‐scales factors are crucial for understanding species richness of Mediterranean riparian forests.